A dynamic swift association scheme for wireless body area networks. Issue 2 (12th August 2019) - Sheraz, Adil; Bangash, Javed Iqbal; Khan, Abdul Waheed; Imran, Muhammad; Khan, Asfandyar; Khan, Abdullah; Ishaq, Muhammad; Khan, Wajid Ullah
Abstract: Among numerous promising applications of wireless sensor networks is wireless body area networks. Wireless body area networks are used for real‐time vital signs monitoring of patients in a remote setting. In addition to their dedicated sensing tasks, the implanted sensor nodes need to effectively utilize their resources to enhance the lifetime of the network. For wireless body area networks, IEEE 802.15.4 low data rate low‐power wireless Personal Area Networks (PANs) standard is adopted. The said standard uses fixed superframe structure operation, which restricts the movement of the nodes, and has degraded performance in the mobility of nodes. Two superframe parameters, ie, beacon order and superframe order, decide the beacon interval and duty cycle of the standard. Both beacon order and superframe order have a strong impact on the performance of network parameters. In this research work, a dynamic swift association scheme is proposed to enhance the performance of a mobile node with a scenario where node moves from its parent PAN and joins the neighbor PAN. Dynamic swift association scheme is compared with IEEE 802.15.4 in terms of association time, association success rate, average throughput, and energy consumption. Simulation results using network simulator version 2 confirm superior performance of dynamic swift association scheme against IEEE 802.15.4 standard. Abstract : Enhances the performance of wireless body area networks thereby supporting seamless connectivity of the body coordinators while hopping from one Personal Area Network (PAN) to neighboring PAN in mobility scenarios.